Effect of the Hope FT-B1 Allele on wheat heading time and yield components - Nitcher, Rebecca; Pearce, Stephen; Tranquilli, Gabriela; Xiaoqin, Zhang; Dubcovsky, Jorge (2017)
Precise regulation of flowering time is critical for plant reproductive success and, in cereals, to maximize grain yields. Seasonal cues including temperature and day length are integrated to regulate the timing of flowering. In temperate cereals, extended periods of cold (vernalization) release the repression of FLOWERING LOCUS T1 (FT1), which is upregulated in the leaves in response to inductive long-day photoperiods. FT1 is a homolog of rice HD3a, which encodes a protein transported from leaves to the shoot apical meristem to induce flowering. A rare FT-B1 allele from the wheat variety “Hope” has been previously shown to be associated with an early flowering phenotype under long-day photoperiods. Here, we demonstrate that the Hope FT-B1 allele accelerates flowering even under short days, and that it is epistatic to the VERNALIZATION 1 (VRN1) gene. On average, the introgression of Hope FT-B1 into 6 genetic backgrounds resulted in 2.6 days acceleration of flowering (P < 0.0001) and 4.1% increase in spike weight (P = 0.0093), although in one variety, it was associated with a decrease in spike weight. These results suggest that the Hope FT-B1 allele could be useful in wheat breeding programs to subtly accelerate floral development and increase adaptation to changing environments.